Direct and indirect effects of age on interoceptive accuracy and awareness across the adult lifespan - Murphy, J; Geary, H; Millgate, E; Catmur, C; Bird, G (Springer US, 2017)
Various aspects of physical and mental health have been linked to an individual’s ability to perceive the physical condition of their body (‘interoception’). In addition, numerous studies have demonstrated a role for interoception in higher-order cognitive abilities such as decision-making and emotion processing. The importance of interoception for health and typical cognitive functioning has prompted interest in how interoception varies over the lifespan. However, few studies have investigated interoception into older adulthood, and no studies account for the set of physiological changes that may influence task performance. The present study examined interoception from young to very late adulthood (until 90 years of age) utilising a self-report measure of interoception (Study One) and an objective measure of cardiac interoception (Study Two). Across both studies interoception decreased with age, and changes in interoceptive accuracy were observed which were not explained by accompanying physiological changes. In addition to a direct effect of age on interoception, an indirect effect of ageing on cardiac interoceptive accuracy mediated by body mass index (BMI) was found, such that ageing was associated with increased BMI which was, in turn, associated with reduced interoceptive accuracy. Such findings support and extend previous research demonstrating interoceptive decline with advancing age, and highlight the importance of assessing whether decreasing interoceptive ability is responsible for some aspects of agerelated ill-health and cognitive impairment.